PENDAMPINGAN PRODUKSI YOGHURT UNTUK PENINGKATAN NILAI JUAL SUSU KELOMPOK TANI TERNAK SAPI (KTTSP) DESA SITU UDIK, CIBUNGBULANG, BOGOR - Hutagaol, Ricson Pemimpin; Susanty, Devy; Rumna, Rumna; Widhyastini, I Gusti Ayu Manik; Wardhani, Gladys Ayu Paramita Kusumah; Oksari, Ade Ayu (Universitas Nusa Bangsa, 2024)
The Bogor Regency dairy cattle livestock business area (KUNAK) is in Cibungbulang District, one of the livestock areas, and the product is cow's milk. The cow's milk produced is sold directly to consumers or milk producers. The selling value of fresh cow's milk is lower than processed cow's milk, and fresh cow's milk has the risk of being easily damaged, resulting in losses for farmers. This Community Service (PKM) activity aims to assist farmers in handling their processed milk production by making yogurt for the Cattle Farmers Group (KTTSP). The approach is in the form of an initial survey regarding partner problems, formulating solutions, providing assistance, and analyzing the partner's level of understanding. This community service activity results in an increase in partners' knowledge of dairy products and how to make them before and after the activity. Apart from that, partners can also increase the selling value of pure cow's milk through processed products in the form of yogurt with a delicious taste and attractive packaging, thereby increasing the selling value of the product.